PENGARUH 6-BENZYLAMINO PURINE (BAP) DAN 6-FURFURYL AMINO PURINE (KINETIN) PADA MEDIA MS TERHADAP PERTUMBUHAN EKSPLAN UJUNG APIKAL TANAMAN JATI SECARA IN VITRO - ROSSA LINA, FARAH Rossa; Wahyono, Rahmad (Universitas Negeri Surabaya, 2013)
Teak is one of economic wood plants, the lack of teak supply has encouraged the expansion of teak plantation. To support the availability of plant material, propagation by tissue culture technique being a good alternative for mass production. This research was aimed at studying the responses of shoot induction and callus of top shoot of teak as result of effect of type of growth regulators, which is BAP and kinetin at MS medium through in vitro method. The study was conducted in the Laboratory Tissue Culture Nursery Permanent (KBP) Department of Agriculture and Forestry Lamongan, with BAP 1 ppm and kinetin 1 ppm on MS medium for callus growth and bud from the apical tip explants teak. Results showed that the growth response of explants apical end teak into callus and shoots. Callus growth on the third day after inoculation and shoots growth on the thirteen day after inoculation. The percentage of explant?s growth on this research is 60.46%; one that consisting of percentage of callus growth is 23.64%, the percentage growth of shoots is 12.79% and explant?s percentage that barren callus and also shoots is 24.03%.